The Factors of Adolescent Depression in Jiangsu Province, China, from the Perspective of Social Ecosystem: A Case-Control Study - Xu, Hua; Chen, Zhao-hong; Ji, Jin-jie; She, Juan; Hou, Chun-ting; Zhang, Yan-hong (Depression and Anxiety, 2023)
Background. The prevalence of adolescent depression is continuously increasing, impacting the cognitive, emotional, and behavioral development of adolescents. Therefore, it is crucial to comprehend depression from the perspective of the social ecosystem, necessitating further empirical evaluation. Methods. This study utilized a case-control study design. The cases consisted of adolescents with depression (aged 13–18 years) admitted to a psychiatric hospital in Nanjing, Jiangsu Province, China, from November 2021 to July 2022, meeting the diagnostic criteria for depression in the 11th Edition of the International Classification of Diseases. Control group students, with a matching gender ratio in the same region, were randomly recruited. Logistic regression analysis was employed to investigate the factors associated with depression, with gender and age as covariates. Results. The study comprised 200 participants, with 44 (22.0%) males and 156 (78.0%) females. Multiple logistic regression analysis revealed that increased adolescent depression was associated with being an only child (AOR=2.680, 95% CI: 1.106–6.492), living in urban areas (AOR=3.324, 95% CI: 1.077–10.267), experiencing school bullying (AOR=9.087, 95% CI: 2.044–40.408), having severe family dysfunction (AOR=6.491, 95% CI: 1.109–37.995), and possessing low core self-evaluation (AOR=11.746, 95% CI: 3.305–41.746). Odds ratios for each factor were statistically significant. Conclusions. Our results improve the evidence for associations between adolescent depression and core self-evaluation, school bullying, family function, living in urban areas, and being an only child. These findings should be taken into consideration in the assessment, intervention, and related policies for adolescent depression.